A LINGUISTIC APPROACH TO CHARACTER INTERACTION: SPEECH STYLE AS A REFLECTION OF SOCIAL IDENTITY IN THE SHORT STORY YUMMY, HAPPY, GOOD-TIME SOUP! - Ade Dwi Cahyanti (Program Studi Pendidikan Bahasa Inggris, 2025)
Language enables us to make sense of everything in the world, from the most basic to the most complex matters. It provides a means for speakers to communicate openly with their listeners. To ensure that interlocutors understand the speech, the speaker must convey it effectively by paying attention to language structure, word choice, intonation, and other factors to prevent misunderstandings by learning speech style. This research focused to find out the types of speech style that occurred in the short story. The researcher applied Martin Joos's (1967) theory of speech styles to explore the types of speech styles used by characters in the short story “Yummy, Happy, Good Time Soup”. This research used qualitative methods to gain information about the speech style of the characters. The study focused on finding out types of speech styles, such as frozen style, formal style, consultative style, casual style, and intimate style, particularly in the short story entitled “Yummy, Happy, Good Time Soup!” Hence, in this research, the data came from the script of a short story performed by three characters namely Mabel, Old Lady namely Mabel, and Mabel’s Mom namely Mabel. The researcher found out that in the dialogue between Mabel, the Old Lady, and Mabel's Mom, three speech styles were observed: formal, consultative, and casual. The formal style appeared once, the casual style appeared seven times, and the consultative style also appeared once. Notably, the casual style was the most frequently used.